Analisis Pengaruh Strategi Pemasaran Online terhadap Keputusan Pembelian Konsumen - Aman, Yosanda Zata; Kustiani, Lilik; Widiawati, Diah; Zakiyah, Wardatuz (Syntax Literate, 2024)
In this digital era, the internet has become an essential part of human life, including in the business world. This has encouraged the emergence of various online marketing strategies used by companies to reach consumers. The purpose of this study is to examine the effect of online marketing strategies on consumer purchasing decisions. This study uses quantitative research methods. The research population is consumers who purchase products or services online. The research sample was 200 consumers selected using random sampling technique. The data that has been collected is then analyzed using the help of the SPSS program. The results showed that online marketing strategies have an effect on consumer purchasing decisions. Therefore, companies need to pay attention to the online marketing strategies used to reach consumers and increase sales.